Does the International Labour Movement Need Salvaging?: Communism, Labourism, and the Canadian Trade Unions, 1921-1928 - Manley, John (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1998)
Abstract Until the Communist Party of Canada (CPC) turned to the tactic of Class Against Class in 1928-29, it confined its trade-union work almost wholly to "boring from within" the international craft unions of the American Federation of Labor/Trades and Labour Congress of Canada. Although "the party" played a dominant part in the very limited industrial conflict of the 1920s, its attempt to transform the international unions into organs of class struggle was wholly unsuccessful, in part because its "line" presumed a far higher degree of rank and file combativeness than actually existed, and in part because Canadian "labourists" actively resisted its best efforts. Where the CPC believed that the international unions needed to be "renovated," the internationals themselves disagreed. Socialist Plumbers' official John W. Bruce posed the question "Does the International Labour Movement need Salvaging?" which he then answered — to general labourist approval — by reaffirming the progressive character of craft unionism and its tried and tested,non-revolutionary methods. The party's failure to break through this complacency — and labourists' growing resentment of its attempts to do so — predisposed it toaccept the Comintern's "New Line" in 1928.